Taxonomic Reassessment of an Enigmatic Flying Frog (Amphibia: Rhacophoridae) from Sangihe Island, Indonesia - Herlambang, Alamsyah Elang Nusa; Sabinhaliduna, Efendi; Trilaksono, Wahyu; Anita, Syahfitri; Riyanto, Awal; Hamidy, Amir; Krone, Isaac; Amini, Sina; Méndez, María José Navarrete; Herr, Mark; Mcguire, Jimmy A. (Zootaxa, 2025)
Sangihe is the northernmost island in a string of a volcanic islands that extend northward from Sulawesi toward the Philippines. Sangihe is known to host one species of flying-frog in the genus Rhacophorus, which is currently classified as a subspecies of the widespread species, R. pardalis (as R. p. rhyssocephalus). Based on newly collected material obtained during a recent expedition in Sangihe, we re-evaluated the taxonomic status of R. p. rhyssocephalus. Molecular sequences (12S rRNA, tRNA val, and 16S rRNA) were obtained for this species, and 66 additional Rhacophorid sequences were extracted from GenBank, including R. pardalis from Borneo. Our molecular analysis revealed that R. p. rhyssocephalus is sister to the Sulawesi Rhacophorus clade, and is not closely related to the widespread lineage of R. pardalis. Furthermore, R. pardalis and R. p. rhyssocephalus exhibit an uncorrected patristic distance of 16%. Our morphological comparisons also identified unique differences between Sangihe and Bornean populations of R. pardalis, such as a prominent U-shaped intraorbital ridge present in the Sangihe population but absent in Bornean population. Based on the available evidence, we elevated the taxonomic status of the Rhacophorus frog from Sangihe Island to Rhacophorus rhyssocephalus. This study highlights the taxonomic complexities and significant discoveries still to be made on this remote island, enhancing our understanding of insular evolutionary processes in this under-explored island archipelago.